2017
DOI: 10.1111/efp.12332
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the spread of Dothistroma septosporum in Europe

Abstract: Dothistroma needle blight (DNB), a disease affecting several pine species, is currently generating great concern in Europe. Caused by Dothistroma pini and Dothistroma septosporum, DNB affects pine needles and causes premature defoliation, which results in growth reduction and, in extreme cases, mortality. The disease has increased in importance in Europe over the last 20 years, with an increase in the number of observations of DNB in regions with large areas of Pinus sylvestris in northern Europe. This article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Our study ignored the expected growth increase of boreal forests under the climate change (Kellomäki et al 2008). It also ignored the expected increases in various potential abiotic and biotic risks to forests, which could at least partly cancel the expected increase in forest productivity under climate change (Valinger and Lundqvist 1992;Peltola et al 2010;Pukkala et al 2014b;Subramanian et al 2016;Thom and Seidl 2016;Möykkynen et al 2017;Reyer et al 2017). For example, the higher share of Norway spruce might lead to a larger risk of biotic and abiotic damages (Kellomäki et al 2008;Peltola et al 2010;Subramanian et al 2016;Thom and Seidl 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Our study ignored the expected growth increase of boreal forests under the climate change (Kellomäki et al 2008). It also ignored the expected increases in various potential abiotic and biotic risks to forests, which could at least partly cancel the expected increase in forest productivity under climate change (Valinger and Lundqvist 1992;Peltola et al 2010;Pukkala et al 2014b;Subramanian et al 2016;Thom and Seidl 2016;Möykkynen et al 2017;Reyer et al 2017). For example, the higher share of Norway spruce might lead to a larger risk of biotic and abiotic damages (Kellomäki et al 2008;Peltola et al 2010;Subramanian et al 2016;Thom and Seidl 2016).…”
Section: Discussionmentioning
confidence: 99%
“…CA are self-organizing systems, which have been used for many purposes (Von Neumann 1966;Wolfram 2002). In forestry, CA have been used for land allocation and planning (Strange et al 2001;, and for simulating the spread of pests and pathogens (Möykkynen and Pukkala 2014;Möykkynen et al 2015Möykkynen et al , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…The current increase in the incidence, range and severity of DNB and other pine needle diseases in Europe may be caused by global climate change (Adamson et al., 2018; Drenkhan et al., 2016; Jánošíková‐Hečková et al., 2018; Mesanza et al., 2019; Mullett et al., 2018; Ondrušková et al., 2017). Over the past two decades, climatic conditions seem to become increasingly favourable for DNB outbreaks in the Northern Hemisphere, and the risk of this disease to Scots pine forests in the boreal region may increase significantly in the future (Möykkynen, Fraser, Woodward, Brown, & Pukkala, 2017; Sturrock et al., 2011; Watt, Ganley, Kriticos, & Manning, 2011; Watt et al., 2009; Woods et al., 2016). Dothistroma needle blight is particularly sensitive to temperature and water availability, the optimal conditions for the development and sporulation of the pathogen is a combination of temperature 15–20/10–12°C (days/nights) with constant humidity and an average daily relative humidity above 90% (Dvorak, Drapela, & Jankovský, 2012; Woods et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A model of the possible impact of climate change on the composition of tree species in Lithuania for 2061–2090 (Ozolinčius et al., 2014) has shown that by the end of this century the climate may become less suitable for Pinus sylvestris and other conifers, and warming of the climate will negatively affect their resistance to diseases and pests. Models of D. septosporum distribution for 2030 in Europe (Möykkynen et al., 2017) also showed that new DNB outbreaks may occur in the future in the Nordic and Baltic countries, Scotland and Ireland, including northern Germany, Poland and Belarus, in regions covered by extensive areas of Scots pine forests, especially where P. sylvestris is planted in monocultures.…”
Section: Discussionmentioning
confidence: 99%